A FDEM 3D moisture migration-fracture model for simulation of soil shrinkage and desiccation cracking. (December 2021) - Yan, Chengzeng; Zheng, Yuchen; Ke, Wenhui; Wang, Gang
Abstract: This paper proposes a three-dimensional moisture migration model, which can simulate the moisture migration process in soil. A simple moisture transport example with analytic solutions is given to verify the correctness of the 3D moisture migration model. Combining the moisture migration model with the combined finite discrete element method (FDEM), a moisture migration-fracture model that simulates soil shrinkage and cracking is constructed and implemented in an in-house GPU parallel multiphysics finite element-discrete element software, namely MultiFracs. The calculation process of the three-dimensional moisture migration-fracture model is: first obtain the moisture field distribution of the solution domain through the moisture migration model; then obtain the shrinkage stress in all tetrahedral elements according to the change of the moisture field; finally, apply the shrinkage stress as a load to perform the deformation and fracture calculations of FDEM. The 3D moisture migration-fracture model is used to simulate an experiment of clayey soil shrinkage cracking. Image recognition technology is used to carry out quantitative statistics and analysis of desiccation crack patterns. The simulation results show high consistency with the laboratory experiment. Moreover, the influences of shrinkage parameter, water evaporation rate, and layer thickness on clayey soil desiccation cracking are studied comprehensively.